Development of a group and family‐based cognitive behavioural therapy program for youth at risk for psychosis. Issue 6 (13th January 2015) - Landa, Yulia; Mueser, Kim T.; Wyka, Katarzyna E.; Shreck, Erica; Jespersen, Rachel; Jacobs, Michael A.; Griffin, Kenneth W.; van der Gaag, Mark; Reyna, Valerie F.; Beck, Aaron T.; Silbersweig, David A.; Walkup, John T.
Abstract: Objective: The onset of psychosis typically occurs during adolescence or early adulthood and can have a detrimental impact on social and cognitive development. Cognitive behavioural therapy (CBT) shows promise in reducing the risk of psychosis. Teaching families to apply CBT with their offspring may bolster therapeutic gains made in time‐limited treatment. We developed a comprehensive group‐and‐family‐based CBT (GF‐CBT) program that aims to facilitate psychosocial recovery, decrease symptoms and prevent transition to psychosis in youth at risk. GF‐CBT is grounded in ecological systems and cognitive theories, resilience models and research on information processing in delusions. The theoretical rationale and description of GF‐CBT are presented together with a pilot study that evaluated the program's feasibility and explored participants' outcomes. Methods: Youth ages 16–21 at risk for psychosis and their families participated in an open trial with pre, post and 3‐month follow‐up assessments conducted by an independent evaluator. The Comprehensive Assessment of At‐Risk Mental States was the primary clinical outcome measure. Results: All enrolled participants ( n = 6) completed GF‐CBT and all remitted from at‐risk mental state (ARMS). As a group participants showed statistically significant decreases in attenuated psychotic symptoms, negative symptoms, depression, cognitive biases and improvements in functioning. Family members showed significant improvements in use of CBT skills, enhanced communication with their offspring, and greater confidence in their ability to help. Gains were maintained at follow‐up. Conclusions: GF‐CBT may delay or prevent transition to psychosis in youth at risk, and potentially facilitate recovery from ARMS. More rigorous, controlled research is needed to further evaluate this program.